Predictors of Health Seeking Behaviours for Common Childhood Illnesses in Poor Resource Settings in Zambia, A Community Cross Sectional Study - Golden Apuleni; Choolwe Jacobs; Patrick Musonda (Frontiers Media S.A., 2021)
Background: Developing countries, including Zambia, account for larger share of child morbidities and mortalities due to common childhood illnesses. Studies on wider determinants of behaviour pertaining to treatment seeking for childhood febrile illnesses in poor resource settings are limited. This study investigated health seeking behaviours of mothers in poor resource settings of Zambia and identified associated factors.Methods: Secondary data from a community cross sectional study design from the Health for the Poorest Population (HPP) Project was analysed between March and May 2019. Data was collected between May and August, 2013. It was collected by means of administering a structured questionnaire from the mothers of under-five children. The survey took place in Samfya and Chiengi of Luapula province while in Northern Province, Luwingu and Mungwi were settled for. A total of 1 653 mothers of under 5 years who had an episode of diarrhoea, malaria, pneumonia or a combination of any of them not more than 14 days before the interview were included in the study. A sample size was arrived at using A Lot Quality Assurance Sampling (LQAS) method. In order to determine the associations between respondent's demographic characteristics and health seeking behaviour, chi square test of independence was carried out. Multivariable logistic regression was also done to identify predictors of health seeking behaviours for common childhood illnesses in children aged <5 years old in poor resource settings.Results: Among the mothers interviewed, 64.6% were married while 35.4% were unmarried. Their mean age was 32 years. Mothers who took their sick children to the health facilities for the purpose of seeking health care for their child for either of the illnesses accounted for 75.2%, [95% CI: 0.62-0.96], while 24.8% did not seek health care for their sick child. Factors typically associated with health seeking behaviours were mothers' marital status [aOR = 0.74; 95% CI: 0.58-0.94], and mothers 'education level [aOR = 1.47; 95% CI: 1.13-1.92].Conclusion: It was established in this study that health care seeking behaviours for these common childhood illnesses in poor resource settings was relatively high and could be predicted by mother's education level and mothers' marital status. Integrating interventions targeted at increasing utilisation of maternal and child health services with basic education to women and moral support counselling to families may potentially maximise health seeking behaviours in marginalised communities.